An anchoring technique by looping with the tip of a super-stiff wire: may be a solution in patients with anomaly of the aortic arch and tortuous carotid artery disease?. (11th December 2013) - Barutcu, Ahmet; Gazi, Emine; Aksu, Feyza; Tatli, Ersan
Abstract : Vascular anatomy is one of the most important factors for the successful carotid artery interventions, either angioplasty or stenting. We report a new technique for advancing a guiding catheter into the common carotid artery when there is an unfavourable aortic arch anatomy and tortuosity of the carotid artery.